Prognostic impact of plasma level of NT-pro BNP in patients with microvascular angina – a report from the international cohort study by COVADIS. (3rd October 2022) - Shimokawa, H; Suda, A; Takahashi, J; Ong, P; Ang, D; Berry, C; Camici, P; Crea, F; Kaski, J; Pepine, C; Rimoldi, O; Sechtem, U; et al.
Abstract: Aims: Although the importance of microvascular angina (MVA) has been emerging, prognostic biomarkers for MVA remain to be developed. We thus aimed to examine whether plasma level of N-terminal prohormone of brain natriuretic peptide (NT-pro BNP) could predict the prognosis of MVA patients. Methods: In the international prospective cohort study of MVA patients by the Coronary Vasomotor Disorders International Study (COVADIS) group, we evaluated the association between plasma level of NT-pro BNP and the incidence of major adverse cardiovascular events (MACE), including cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, and hospitalization due to heart failure or unstable angina. Results: We examined a total of 226 MVA patients (M/F 66/160, 61.9±10.2 [SD] years) with both plasma NT-pro BNP levels and echocardiographic data in the COVADIS study. Plasma NT-pro BNP level was elevated (median 94 pg/ml, IQR 45–190) while mean LVEF (69.2±10.9%) and E/e' (10.7±5.2) were almost normal. During follow-up period of a median of 365 days (IQR 365–482), 29 MACEs occurred. ROC curve analysis identified plasma NT-pro BNP level of 78 pg/ml as the optimal cut-off value. Multivariable logistic regression analysis revealed that plasma NT-pro BNP level ≥78 pg/ml significantly correlated with the incidence of MACE (odds ratio (OR) [95% confidence interval (CI)] 3.11 [1.14–8.49], P=0.03). When divided into 2 groups by NT-pro BNP 78 pg/ml, the Kaplan-Meier survival analysis showed a significantly worse prognosis in the group with NT-pro BNP ≥78 (log lank, P=0.03) (Figure). Conclusions: These results indicate that plasma NT-pro BNP level is a novel prognostic biomarker for MVA patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Japan Heart Foundation